ROLE PEFORMANCE LIBRARIAN IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 : OPTIMIZING PUBLIC LIBRARY SERVICE QUALITY IMPROVEMENT IN ORDER TO FULFILL INFORMATION NEEDS IN A SOCIOLOGICAL PERSPECTIVE - BAKHTIYAR (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The research intends to describe the role of librarians in meeting the information needs of society. The object of research is focused on analyzing studies based on a comprehensive, detailed discussion of content is very urgent, is a fundamental investigation of the role of librarians in improving the quality of public library services to fulfill user satisfaction, given that information needs are increasingly developing with very rapidly.The research has the scope of in-depth analysis, based on the focus of the study of optimizing the improvement of the quality of public library services in order to fulfill user satisfaction with information, which is felt to have increased rapidly and information search has turned digital. Research analysis requires realistic but critical thinking, applying a concept in the historical period in the past or is happening, then it is appropriate to apply the historical approach, characterized by the dominance of critical investigation of the development of a thought or term. Primary information sources are empowered as primary data. Collecting data utilizes a research library, through reading various literatures on the subject of the role of public libraries, service quality, and community information needs. Qualitative descriptive analysis is based on the analysis of various theoretical reading materials, research and non-research. Research dominates very evaluative descriptions of factual facts, for solutions to problematic solutions to social phenomena, the role of public libraries in meeting community needs. Research validity is realized, bypassing content analysis, analyzing the meaning of important concepts. Observations of librarian performance activities in public libraries are used to support theory construction. The results showed that librarians have a strategic position and play an active role in improving the quality of information services to meet community needs. Automatically, librarian's role performance is highly expected by the library users, able to be realized by librarians so that they can take an active role in carrying out excellent public library services.